In-vivo Sino-Atrial Node Mapping in Children and Adults With Congenital Heart Disease - Kharbanda, Rohit K.; van Schie, Mathijs S.; Ramdat Misier, Nawin L.; Wesselius, Fons J.; Zwijnenburg, Roxanne D.; van Leeuwen, Wouter J.; van de Woestijne, Pieter C.; de Jong, Peter L.; Bogers, Ad J. J. C.; Taverne, Yannick J. H. J.; de Groot, Natasja M. S. (Frontiers in Pediatrics, 2022)
Background: Sinus node dysfunction (SND) and atrial tachyarrhythmias frequently co-exist in the ageing patient with congenital heart disease (CHD), even after surgical correction early in life. We examined differences in electrophysiological properties of the sino-atrial node (SAN) area between paediatric and adult patients with CHD. Methods: Epicardial mapping of the SAN was performed during sinus rhythm in 12 paediatric (0.6 [0.4-2.4] years) and 15 adult (47 [40-55] years) patients. Unipolar potentials were classified as single-, short or long double- and fractionated potentials. Unipolar voltage, relative R-to-S-amplitude ratio and duration of all potentials was calculated. Conduction velocity (CV) and the amount of conduction block (CB) was calculated. Results: SAN activity in paediatric patients was solely observed near the junction of the superior caval vein and the right atrium, while in adults SAN activity was observed even up to the middle part of the right atrium. Compared to paediatric patients, the SAN region of adults was characterized by lower CV, lower voltages, more CB and a higher degree of fractionation. At the earliest site of activation, single potentials from paediatrics consisted of broad monophasic S-waves with high amplitudes, while adults had smaller rS-potentials with longer duration which were more often fractionated. Conclusions: Compared to paediatric patients, adults with uncorrected CHD have more inhomogeneous conduction and variations in preferential SAN exit site, which are presumable caused by ageing related remodelling. Long-term follow-up of these patients is essential to demonstrate whether these changes are related to development of SND and also atrial tachyarrhythmias early in life.